2004
DOI: 10.1111/j.1365-2621.2004.tb06320.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cell Wall Enzyme Activities, Pectin Composition, and Technological Criteria of Strawberry Cultivars (Fragaria×ananassaDuch)

Abstract: The effects of physical characteristics and cell wall enzymatic activities of several strawberry cultivars were investigated for possible industrial use. The enzymes study showed that the softest varieties had the highest pectin methylesterase (PME) and polygalacturonase (PG) activities. Differences in alcohol-insoluble pectin, water-soluble pectin, and parietal residue compositions were observed between Darsanga ("firm fruit") and Senga sengana ("soft fruit"). Finally, the study of pectin composition of Darsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
1
12
0
4
Order By: Relevance
“…Similar values were found by Duvetter et al (2005a) (DM = 79%), while Lefever et al (2004) reported somewhat lower values (DM = 67-75%). Pectin in strawberries that were infused with PME+Ca 2+ had a lower DM, indicating that PME had acted on the pectin.…”
Section: Degree Of Methoxylation and Pectin Content Of Airsupporting
confidence: 92%
“…Similar values were found by Duvetter et al (2005a) (DM = 79%), while Lefever et al (2004) reported somewhat lower values (DM = 67-75%). Pectin in strawberries that were infused with PME+Ca 2+ had a lower DM, indicating that PME had acted on the pectin.…”
Section: Degree Of Methoxylation and Pectin Content Of Airsupporting
confidence: 92%
“…In the two independent lines analyzed, transgenic antipectate lyase fruits withstand better the cooking process resulting in an increased content of whole berries in jam. Content of whole berries after cooking in the presence of sugar is one of the most representative quality criteria of processed strawberry (Haffner, 2002;Lefever et al, 2004). The higher values of firmness observed in fresh transgenic fruits when compared with control were also maintained after being processed the fruits.…”
Section: Discussionmentioning
confidence: 57%
“…Contrary to these research findings, Villarreal et al (2008) recently found that PG activity increases in strawberry fruit during development and that total PG activity correlates positively with fruit softening. Similarly, Lefever et al (2004) found that softness in strawberry varieties correlated positively with PG activity in ripening fruits. At the molecular level, three ripening-related PG genes have been cloned.…”
Section: Discussionmentioning
confidence: 99%